Implementasi Modul Ajar di Sekolah SMP N 12 Palangka Raya dalam Mata Pelajaran PAK Kelas VIII SMP - Triani Cahya Ningsih; Rike Yulianingsih; Prita Aura Eklesia; Matius Timan Herdi Ginting (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2025)
The implementation of the eighth-grade Christian Religious Education teaching module on the topic "Love as the Foundation of a Believer's Life" was carried out as an effort to provide an active, reflective, and contextual learning process in accordance with the principles of the Independent Curriculum. Learning is designed through an interactive approach with discussion activities, analysis of biblical texts, case studies, problem-solving, and personal reflection that provide opportunities for students to construct understanding independently. Through these activities, students are guided to understand the concept of agape love as sincere love, giving without expecting anything in return, and is manifested in concrete actions towards others. The implementation results show that this teaching module is able to improve students' conceptual understanding of the meaning of love from a biblical perspective and its relevance in modern life. Students appear to be increasingly confident in expressing opinions, are able to work together in groups, and are actively involved in learning activities. In addition, the emergence of attitudes of empathy, tolerance, and habits of helping each other are indicators that the value of love is not only understood cognitively, but also internalized in behavior. This teaching module also contributes to improving students' critical thinking skills and spirituality through reflection activities that invite them to evaluate acts of love in daily life at school, family, and society.